2019
DOI: 10.3390/horticulturae5010015
|View full text |Cite
|
Sign up to set email alerts
|

Timing of a Short-Term Reduction in Temperature and Irradiance Affects Growth and Flowering of Four Annual Bedding Plants

Abstract: Heating and supplemental lighting are often provided during spring greenhouse production of bedding plants, but energy inputs are a major production cost. Different energy-savings strategies can be utilized, but effects on plant growth and flowering must be considered. We evaluated the impact and timing of a two-week low-energy (reduced temperature and irradiance) interval on flowering and growth of impatiens (Impatiens walleriana Hook.f. ‘Accent Orange’), pansy (Viola × wittrockiana Gams. ‘Delta Premium Blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In particular, flowering was delayed, and reductions in flower number, plant size, and biomass were observed. The most affected crops where those that were cold-sensitive, such as impatiens [5]. Further, studies should be carried out on cold tolerant species and in non-flowering species.…”
Section: Controlled Abiotic Stress Management For the Agriculture Promentioning
confidence: 99%
“…In particular, flowering was delayed, and reductions in flower number, plant size, and biomass were observed. The most affected crops where those that were cold-sensitive, such as impatiens [5]. Further, studies should be carried out on cold tolerant species and in non-flowering species.…”
Section: Controlled Abiotic Stress Management For the Agriculture Promentioning
confidence: 99%
“…Usually, after completing of juvenile and developmental phases plants go through reproductive phase responding to the environmental factors (temperature, photoperiod). The literatures related to the winter annuals like effects of differential temperature on the growth, morphology and flowering of Antirrhinum majus, flower production of calendula, growth and flowering of Californian poppy, Helichrysum bracteatum, Coreopsis, Cornflower, Sweet Williams (Krogt, 1980;Kanamadi et al, 1999;Kazinczi et al, 1999;Shang et al, 2003;Mili & Sable, 2003;Singh, 2005;Dhatt & Kumar, 2007;Ibrahim et al, 2010), flower initiation and development of Petunia and Viola (Mattson & Erwin, 2003), responds of Calendula, Chrysanthemum, Pansy and Snapdragon to high temperatures, impact of reduce temperature and irradiance flowering and growth of four annual bedding plants (Warner & Erwin, 2006;Boldt & Atland, 2019) and assessment of height, earliness and biomass production in winter annuals (Bhattarai et al, 2019) revealed the variation on plant height, growth habit, shape, size, color of flowers, time and duration of flowering within the genotypes, even though these are the species of same growing season. But reports regarding the comparative study and the performance of diverse winter ornamental annuals under different growing environments are in scarcity.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the highest light incidence was, on average, 40 minutes before the highest air temperature (Figure 3A), as it is necessary to heat and occur the emission of long waves (thermal) from the soil to heat the air. Besides promoting photosynthesis, the light incidence influences the growth of crops and the gain of dry matter, and, combined with temperature, affects the cycle of crops and the quality of harvested products (Boldt and Altland, 2019).…”
mentioning
confidence: 99%